Exploring the association between grade point average and work engagement: insights from a cross-sectional study of medical students - Huang, Runzhi; Zhou, Jiajie; Chen, Yang; Zhang, Wei; Lin, Min; Gong, Meiqiong; Lu, Bingnan; Jin, Minghao; Yao, Yuntao; Lu, Yuwei; Tong, Xirui; Lu, Jianyu; et al. (Frontiers in Medicine, 2025)
BackgroundMedical students’ work engagement (MSWE) is widely considered an essential indicator of their state of mind, affecting their productivity and future career development as doctors. In our previous research, grade point average (GPA) was demonstrated to be an independent predictor of self-regulated learning (SRL), which is closely associated with MSWE. However, the relationship between GPA and MSWE has not been systematically elucidated. Our study aims to discover and clarify the significant association between GPA and MSWE.MethodsWe collected data from 12 universities in China and evaluated MSWE using the Utrecht Work Engagement Scale (UWES). Then, we conducted a cross-sectional study where GPA and UWES scores or categories were recorded simultaneously. Pearson’s chi-squared tests and Welch’s ANOVA were utilized to explore the distributional association between GPA and MSWE. Multivariate logistic regression analysis was performed to examine whether GPA was a significant factor of MSWE, followed by a subgroup analysis to exclude other confounding factors. Ultimately, GPA was used as a key variable to develop a nomogram aimed at evaluating the possibility of low UWES scores, along with calibration and accuracy assessments.ResultsPearson’s chi-squared tests (p = 2.54e-65) and Welch’s ANOVA (p = 8.07e-48) demonstrated a strong association between GPA and UWES scores, indicating a significant relationship with MSWE. Medical students with a GPA in the “top 5%” and “5–20%” categories exhibited a higher level of MSWE. Multivariate analysis revealed that GPA was statistically significant across all rank categories (all p < 0.001), thereby + GPA’s significance in factoring MSWE. In addition, statistical significance persisted in subgroup analysis, which excluded the confounding effect of age and gender. Ultimately, the nomogram was validated as accurate and reliable (area under the curve (AUC) = 0.626), providing a quantitative assessment of MSWE primarily based on GPA.ConclusionMedical students with higher GPA scores tended to exhibit better MSWE. GPA was strongly validated as a significant factor in evaluating MSWE.